Cytotoxic Effect of Rhopalurus junceus Scorpion Venoms on the HeLa Cell Line (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: Rhopalurus junceus scorpion venom; female; male; mixture of two sexes; heLa